2018
DOI: 10.21061/jvs.v3i2.49
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Military Friendly in Organizations: An Empirical-based Definition

Abstract: Employers interested in hiring military veterans are increasingly using the "military friendly" or "veteran-friendly" labels to promote their organizations to job-seeking veterans. The terms, while inviting to veterans, lack definition and consistency across organizations, leading to ambiguity about what it means to be military or veteran friendly. This research sought to understand how the labels are being supported through corresponding initiatives and, more generally, identify commonalities across employers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…While the U.S. Department of Labor's Bureau of Labor Statistics (2020) reports the post‐9/11 veteran unemployment rate of 4.4% in January 2020, it still sits higher than the civilian rate of 3.1% for civilian non‐veterans for that same period. Employers seeking to promote a veteran‐friendly organizational profile have offered employment to many veterans who want civilian employment, but many low‐wage entry positions available are more suited to those without any work experience than veterans who have proven their capabilities in military service (Kirchner & Minnis, 2018). What has not been described by employers or probed significantly in research is the way in which veterans integrate culturally to the organizations hiring them.…”
Section: Introductionmentioning
confidence: 99%
“…While the U.S. Department of Labor's Bureau of Labor Statistics (2020) reports the post‐9/11 veteran unemployment rate of 4.4% in January 2020, it still sits higher than the civilian rate of 3.1% for civilian non‐veterans for that same period. Employers seeking to promote a veteran‐friendly organizational profile have offered employment to many veterans who want civilian employment, but many low‐wage entry positions available are more suited to those without any work experience than veterans who have proven their capabilities in military service (Kirchner & Minnis, 2018). What has not been described by employers or probed significantly in research is the way in which veterans integrate culturally to the organizations hiring them.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the results provide a strong response to the call for more empirical research (Batka & Hall, 2016;Haynie, 2016;Kirchner & Minnis, 2018; Society for Human Resource Management, 2017) documenting the impact of veterans in civilian organizations and a powerful argument supporting the business case for hiring veterans. As Batka and Hall (2016, p. 3) noted: "While efforts [to employ veterans] motivated by patriotism or charity may wane over time, those motivated by what is good for business are more likely to endure.…”
Section: Introductionmentioning
confidence: 91%
“…Government agencies and universities are excluded from this competition. The evaluation consists of a more than 100-item survey addressing the following weighted categories (weights listed below are based on the 2015 survey): 2019The methodological rigor and validity of the GI Jobs procedure for determining military friendly organizations was confirmed by Kirchner and Minnis (2018). They reviewed six potential military friendly lists in their empirical study to identify common themes found in military friendly organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Within recent years, there have been a vast amount of organizations striving for the “veteran friendly” designation (Kirchner & Minnis, 2018). According to Ferraro (2016), a veteran friendly organization is one that demonstrates support of veterans in a myriad of capacities, which includes support at the executive level, hiring process, community outreach, shared beliefs, and value of veterans at an organizational level.…”
Section: Recruitment Of Veterans For the Civilian Organizationsmentioning
confidence: 99%